A TRANSLATION OF LANGUAGE VS. LITERATURE IN THE ARAB WORLD - Aris Fuadi (Universitas Insan Pembangunan Indonesia, 2021)
Translation is an activity to translate from the source text (ST) or source language (SL) into target text (TT) or target language (TL). Translation use “equivalent” instead of “meaning” as an important language. The translation process has some of opportunities for the writer to develop his/her ability to understand of meaning in language and grammar and also structure of language study.Translation process will help us to increase ability of reading and writing in a translating process. Meanwhile, the writer is very interested in translating an English article is entitled Language vs. Literature in the Arab World into Indonesian because many English students have difficulties to translate it correctly based on its rules and principles.In this paper, the writer would like to translate an English text into Indonesian and find some translation problems and their solution.Keyword : language, literature, English departments, and Arab world